Profile of Mathematics Communication Ability of Seventh-Grade Students in Solving Set Problems Based on Cognitive Style - Kresensia Usolin; Aloisius Loka Son; Talisadika Serrisanti Maifa; Javier García-García (Pendidikan Matematika UNIMOR, 2023)
This study aims to describe the profile of students' mathematical communication ability in solving set problems in terms of field-dependent and field-independent cognitive styles. This research method includes qualitative descriptive research. In this study, the collected data was in the form of words so that it did not emphasize numbers. Participants in this study consisted of three students with a field-dependent cognitive style and three students with a field-independent cognitive style from class VII at one of the junior high schools in North Central Timor Regency. The instruments used are a mathematical communication ability test, Group Embedded Figure Test, and interviews. The results showed that students with a field-independent cognitive style have high mathematical communication abilities. This can be seen from the test results of the three field-independent students who are able to express mathematical ideas through oral, written, demonstration and describe in visual form, are able to analyze, interpret, and evaluate mathematical ideas through oral, written, and other visual forms, and are able to use terms, mathematical notations, and their structures to present ideas, describe relationships, and situation models when solving problems mathematical sets. Meanwhile, students with a field-dependent cognitive style have low mathematical communication abilities. This can be seen from the results of the mathematics communication ability test of the three field-dependent students who have not been able to meet all the indicators of mathematical communication.